Towards Understanding the Relationship Between ER Stress and Unfolded Protein Response in Amyotrophic Lateral Sclerosis - Zhao, Chenxuan; Liao, Yong; Rahaman, Abdul; Kumar, Vijay (Frontiers in Aging Neuroscience, 2022)
Cellular stress induced by the aberrant buildup of unfolded proteins in the endoplasmic reticulum (ER) is considered a key driver in many human neurodegenerative diseases. Cellular adaptation to ER stress is achieved by the activation of the unfolded protein response (UPR), which is an integrated signal transduction pathway that modifies many features of ER physiology. Strong evidence suggests that ER stress plays an important role in the pathogenesis of amyotrophic lateral sclerosis (ALS) through altered regulation of proteostasis. Moreover, accumulating evidence indicates that ER stress and UPR are important players in TDP-43 pathology. In this review, we will explore the complex interplay between ER stress and the UPR in ALS and TDP-43 pathology by breaking down the evidence from in vitro and in vivo models of ALS. We also discuss therapeutic strategies to control levels of ER stress and UPR signaling components that have contrasting effects on ALS pathogenesis.